Exploring Bedroom Usability and Accessibility in Parkinson’s Disease (PD): The Utility of a PD Home Safety Questionnaire and Implications for Adaptations - Bhidayasiri, Roongroj; Jitkritsadakul, Onanong; Sringean, Jirada; Jantanapornchai, Thitiporn; Kantachadvanich, Nitinan; Phumphid, Saisamorn; Boonpang, Kamolwan; Pensook, Sarawan; Aungkab, Nicharee; Hattori, Nobutaka; Chaudhuri, K. Ray (Frontiers in Neurology, 2018)
Background Although bedrooms are identified as a major location for accidents among Parkinson’s disease (PD) patients, there are no studies that specifically evaluate the bedroom environments of PD patients. Objective To examine the physical bedroom environment of patients with PD by generating a home safety questionnaire to rate bedroom accessibility and usability specifically for PD patients, and piloting it in a small set of PD patients, to identify environmental barriers and recommend adaptations to reduce accident risks. Methods Questionnaire development was based on the concept of Personal (P)-Environmental (E) fit. The P component covers five clinical domains that contribute to a patients’ current state of health, including PD-related motor symptoms, PD-related non-motor symptoms, gait and balance impairments, comorbidities, and limitations on specific activities. The E component focuses on both indoor (bedroom, bathroom, living room, stairs, and kitchen), and outdoor (outdoor area and entrance) areas within a home where PD patients commonly get injured. Total score for the whole questionnaire is 171. A higher score indicates more P-E problems. Results Comprehension of questions was tested for content validity with an item-objective congruence index of above 0.6 for all items. High internal consistency (reliability) was confirmed by Cronbach’s alpha coefficient of 0.828 (r). The pilot in five PD patients gave a mean total score of 48.2 ± 7.29 with a mean score on personal and environmental components of 16.8 ± 5.12 and 31.4 ± 4.51, respectively. Conclusion This PD home safety questionnaire is a valid and reliable instrument for examining P-E problems by a multidisciplinary team during their home visits. More studies, involving a large number of PD patients, are needed to establish its utility as a screening instrument in PD patients to assess for home adaptations.